Child Friendly Science Education To Prevent Child Pornography - Bella Marta L.P; Laila Rahmawati; Zulfa Ihzani; Nuri Maulidiyah; Anisa Baroroh; Muhammad Amanuddin (Proceedings of The ICECRS, 2020)
This study examines how the influence of child-friendly Science Education in efforts to prevent Child Pornography. This research is in the form of library research. This research is a qualitative study in which data collection is done by collecting studies from books and scientific journals that are associated with the phenomenon of the rise of pornography in children and adolescents. The collected data were analyzed using a phenomenological approach to determine the effect of child friendly science education in reducing and preventing pornography at the level of children and adolescents. The results of the literature analysis found that child-friendly science learning can prevent pornography at the level of children and adolescents.